The Influence of "UNNES Lantip" Learning Outcomes on The Pedagogical Competency of Culinary Education Program Students From The Class of 2021 - Azzahra, Novianti Sekar Ayu; Bambang Sugeng Suryatna; Pudji Astuti (Jurnal Profesi Keguruan, 2025)
This study aims to determine the effect of UNNES Lantip learning outcomes on the pedagogical competence of Culinary Education students at UNNES class of 2021. The research method used is descriptive quantitative. The population in this study includes all 2021 students who participated in the UNNES Lantip program, with a total sample of 75 respondents selected using a saturated sampling technique. Data were collected through a pedagogical competence questionnaire using a Likert scale and documentation of the final Lantip scores. Data analysis was conducted using a simple linear regression test with the help of SPSS 25. The results show a positive and significant effect of UNNES Lantip learning outcomes on students' pedagogical competence, with a significance value of 0.000 (p < 0.05) and a coefficient of determination (R²) of 0.621. This means that 62.1% of the variation in pedagogical competence can be explained by the UNNES Lantip learning outcomes. These findings indicate that students who achieve high learning outcomes in the Lantip program tend to have better pedagogical abilities, particularly in lesson planning, implementation, evaluation, and student potential development. Therefore, the UNNES Lantip learning outcomes can be said to significantly contribute to shaping the pedagogical competence of students as future professional teachers..